University-Industry Technology Transfer and Innovation Activity in Mexico - Rodríguez, José Carlos (2021)
This paper analyzes the process of university-industry technology transfer (UITT) and innovation activity among universities in Mexico. The objective of this paper is twofold. First, it presents the main results from the University-Industry Technology Transfer Activity survey in Mexico (UITTAM) (UITTAM, 2018). Second, it investigates the process of UITT activity in Mexico, applying the Qualitative Comparative Analysis (QCA) methods developed by C.C. Ragin (1987, 2000, 2006, 2008). In so doing, the QCA model computed in this research makes use of data released from the UITTAM.